Curable composition

By using curable compositions of fluorene-containing (meth)acrylate, sulfur atom-containing (meth)acrylate and nanozirconia particles in optical lens materials, the problem of excessive viscosity of high refractive index materials is solved. , realizes a combination of high refractive index and low viscosity, and is suitable for thin and lightweight optical components.

CN119301166APending Publication Date: 2025-01-10DAICEL CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380044364.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-09
Filing Date
2023-06-05
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the prior art, high-refractive index optical lens materials tend to have too high viscosity, resulting in poor operability and difficulty in taking into account both high-refractive index and low viscosity.

Method used

The curable composition of the fluorene-containing (meth)acrylate, sulfur atom-containing (meth)acrylate and nanozirconia particles is used to adjust the composition of the composition to achieve high refractive index and low viscosity, which is suitable for Optical uses such as wafer lenses.

Benefits of technology

The balance of high refractive index and low viscosity is achieved, the operability and optical properties of the composition are improved, and it is suitable for the manufacture of thin and lightweight optical components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005164342400000031
    Figure BDA0005164342400000031
  • Figure BDA0005164342400000051
    Figure BDA0005164342400000051
  • Figure BDA0005164342400000071
    Figure BDA0005164342400000071
Patent Text Reader

Abstract

Provided is a curable composition which, when formed into a cured product, has a high refractive index and a low viscosity. The curable composition contains a (meth) acrylate containing a fluorene skeleton, a (meth) acrylate containing a sulfur atom, and nano-zirconia particles. Furthermore, the curable composition preferably further contains another monofunctional (meth) acrylate, a radical polymerization initiator, and a reaction retarder, and the refractive index of the curable composition preferably is 1.65 or more and the viscosity preferably is 10,000 mPa.s or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a curable composition, and in particular to a curable composition that can be used for optical applications such as wafer lenses and sensors. In addition, the present application claims priority to Japanese Patent Application No. 2022-094012 filed in Japan on June 9, 2022, the contents of which are incorporated herein by reference. Background Art

[0002] With the development of optoelectronics, thinner and smaller components are required for the lenses of cameras installed in mobile phones, etc., and high refractive index materials are desired for optical lens materials. Furthermore, in order to achieve such a high refractive index, various materials have been added to materials having a fluorene skeleton.

[0003] For example, Patent Documents 1 and 2 disclose curable compositions containing an acrylate having a fluorene skeleton and a (meth)acrylate containing a sulfur atom.

[0004] Patent Document 3 discloses a photocurable high-refractive-index resin composition using an acrylate having a fluorene skeleton and nano-sized zirconium oxide particles in order to increase the refractive index.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2014 / 119424

[0008] Patent Document 2: International Publication No. 2018 / 062196

[0009] Patent Document 3: Japanese Patent Application Publication No. 2019-19245 Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, the refractive index disclosed in the inventions described in Patent Documents 1 and 2 is not sufficient. In the invention of Patent Document 3, although the refractive index is sufficient, on the other hand, there is a problem that the viscosity is too high and the workability is poor, and both a high refractive index and workability are not achieved.

[0012] The present disclosure solves such problems, and an object of the present disclosure is to provide a curable composition having a high refractive index and a low viscosity when a cured product is obtained.

[0013] Solution to the problem

[0014] The present inventors have conducted in-depth research to achieve the above-mentioned purpose, and found that the cured product obtained from the curable composition containing a (meth)acrylate containing a fluorene skeleton, a (meth)acrylate containing a sulfur atom, and nano zirconium oxide particles has a high refractive index, and the curable composition itself has a low viscosity. The present disclosure is completed based on these insights.

[0015] The present disclosure provides a curable composition containing a fluorene skeleton-containing (meth)acrylate, a sulfur atom-containing (meth)acrylate, and nano zirconium oxide particles.

[0016] The curable composition contains a sulfur-containing (meth)acrylate, so that the cured product has a high refractive index and can be made low in viscosity to a level that allows easy handling during casting and injection molding. In addition, the curable composition contains a fluorene skeleton-containing (meth)acrylate and nano zirconium oxide, so that the refractive index can be increased while maintaining a low viscosity.

[0017] In addition, the curable composition preferably contains other monofunctional (meth)acrylates. The curable composition can adjust the viscosity and improve the storage stability by containing the monofunctional (meth)acrylate.

[0018] In addition, the curable composition preferably has a refractive index of 1.65 or more at a wavelength of 589 nm when cured. Such a high-refractive-index curable composition is suitable for imparting functions such as antireflection and optical waveguide when used as a wafer lens.

[0019] The curable composition preferably has a viscosity of 10,000 mPa·s or less at 25° C. The curable composition having such a viscosity can be easily used for casting molding or injection molding and has excellent workability.

[0020] The sulfur-atom-containing (meth)acrylate of the curable composition preferably has a bis(4-(meth)acryloylthiophenyl)sulfide skeleton. The curable composition containing such a compound can easily reduce viscosity.

[0021] In the curable composition, the mode diameter of the nano-zirconia particles measured by particle size distribution measurement is preferably 1 to 100 nm. The curable composition can easily have a refractive index of 1.65 or more by setting the mode diameter of the nano-zirconia particles to 1 to 100 nm.

[0022] Furthermore, the curable composition can be preferably used for wafer lenses.

[0023] Effects of the Invention

[0024] Since the curable composition of the present disclosure has the above-mentioned structure, when it is made into a cured product, it has a high refractive index and can achieve a low viscosity. DETAILED DESCRIPTION

[0025] [Curable composition]

[0026] The curable composition disclosed herein contains a fluorene skeleton-containing (meth)acrylate, a sulfur atom-containing (meth)acrylate, and nano zirconium oxide particles as essential components. It should be noted that in the following description, the fluorene skeleton-containing (meth)acrylate is sometimes referred to as compound (A) (or (A)), the sulfur atom-containing (meth)acrylate is sometimes referred to as compound (B) (or (B)), and the nano zirconium oxide particles are sometimes referred to as compound (C) (or (C)).

[0027] In addition, in this specification, "(meth)acrylic acid" means "acrylic acid" and / or "methacrylic acid" (either or both of "acrylic acid" and "methacrylic acid"), and the same applies to others.

[0028] In addition, the viscosity of the curable composition at 25°C is preferably 10000 mPa·s or less, more preferably 5000 mPa·s or less, and further preferably 3000 mPa·s or less. By making the viscosity of the curable composition below 10000 mPa·s, the curable composition can be easily used for casting and injection molding, and has a tendency to be excellent in operability. The lower limit of the viscosity of the curable composition is not particularly set, for example, it is above 10 mPa·s, preferably above 50 mPa·s, and more preferably above 100 mPa·s. When the viscosity of the curable composition is above 10 mPa·s, it is not easy to flow out from the surface of the substrate after coating.

[0029] <Fluorene skeleton-containing (meth)acrylate (A)>

[0030] Compound (A) is a radical curable compound (a curable compound having free radical polymerizability) containing a (meth)acryloyl group having free radical polymerizability. The number of functional groups in (A) is not particularly limited, but from the viewpoint of producing a polymer having a high refractive index, it is preferably 2 or more functional groups, and in order to have a moderate hardness during curing, it is preferably 4 or less functional groups.

[0031] The curable composition of the present disclosure contains the compound (A), which tends to impart excellent optical properties (transparency, high refractive index) to a cured product obtained by curing the curable composition. Examples of the compound (A) include compounds represented by the following formula (1).

[0032] [Chemical formula 1]

[0033]

[0034] In the above formula (1), ring Z 1 、Ring Z 2 are the same or different and represent an aromatic carbocyclic ring (aromatic hydrocarbon ring). 1 , R 3 are the same or different and represent an alkylene group having 1 to 10 carbon atoms. 2 , R 4 The same or different, represents a hydrogen atom or a methyl group. 1 、p 2 The same or different represents an integer greater than 0.

[0035] As Ring Z 1 、Ring Z 2 The aromatic carbon ring in the ring includes an aromatic carbon ring having about 1 to 4 rings such as a benzene ring, a naphthalene ring, and an anthracene ring. Among them, the aromatic carbon ring is preferably a benzene ring, a naphthalene ring, or the like.

[0036] As R 1 , R 3 The alkylene group in the group includes, for example, a linear or branched alkylene group having 1 to 10 carbon atoms, such as methylene, ethylene, propylene, trimethylene, tetramethylene, and hexamethylene. Among them, the alkylene group is preferably an alkylene group having 2 to 6 carbon atoms, such as ethylene, propylene, and trimethylene, and more preferably an alkylene group having 2 to 3 carbon atoms.

[0037] p 1 、p 2 Each is an integer of 0 or more, preferably an integer of 0 to 4, and more preferably an integer of 1 to 4 from the viewpoint of lower viscosity and better fluidity.

[0038] In formula (1), the fluorene ring and ring Z 1 、Ring Z 2 It may optionally have a substituent. 1 、Ring Z 2 The substituent group optionally possessed includes, for example, alkyl groups such as methyl, ethyl, propyl, and isopropyl (for example, C 1-6 alkyl, preferably methyl); cyclopentyl, cyclohexyl and other cycloalkyl (e.g., C 5-8 cycloalkyl, etc.); phenyl, naphthyl and other aryl groups (e.g., C 6-15 aryl, etc.); arylalkyl such as benzyl (for example, C 7-16 arylalkyl, etc.); acetyl, propionyl, benzoyl and other acyl groups (e.g., C 1-10 acyl, etc.); alkoxy groups such as methoxy, ethoxy, propoxy, isopropoxy, etc. (e.g., C 1-6alkoxy, etc.); alkoxycarbonyl such as methoxycarbonyl and ethoxycarbonyl (for example, C 1-4 alkoxycarbonyl, etc.); cyano; carboxyl; nitro; amino; substituted amino (e.g., mono- or di-C 1-4 halogen atoms such as fluorine atom and chlorine atom, etc.

[0039] Examples of (A) include 9,9-bis[4-((meth)acryloyloxy)phenyl]fluorene and the like 9,9-bis[(meth)acryloyloxyphenyl]fluorene; 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene, 9,9-bis[4-(2-(meth)acryloyloxypropoxy)phenyl]fluorene and the like 9,9-bis[((meth)acryloyloxy) 2-4 9,9-bis[mono- or di-C fluorenes; 9,9-bis[3-methyl-4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene, 9,9-bis[3-methyl-4-(2-(meth)acryloyloxypropoxy)phenyl]fluorene, 9,9-bis[3,5-dimethyl-4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene, etc. 1-4 Alkyl-(2-(meth)acryloyloxy) 2-4 9,9-bis[3,4-bis(2-(meth)acryloyloxyethoxy)phenyl]fluorene, 9,9-bis[3,5-bis(2-(meth)acryloyloxyethoxy)phenyl]fluorene, etc. 9,9-bis[bis(2-(meth)acryloyloxyC 2-4 9,9-bis[3,4,5-tri(2-(meth)acryloyloxyethoxy)phenyl]fluorene, etc. 2-4 Alkoxy)phenyl]fluorene; in the above compounds, C 2-4 Compounds in which an alkoxy group is substituted with a polyalkoxy group (diethoxy, triethoxy, etc.) (9,9-bis[(meth)acryloyloxy C 2-4 9,9-bis[4-(2-(2-(meth)acryloyloxyethoxy)ethoxy)phenyl]fluorene, 9,9-bis[3,5-dimethyl-4-(2-(2-(meth)acryloyloxyethoxy)ethoxy)phenyl]fluorene, etc. 9,9-bis[((meth)acryloyloxy C 2-4 Alkoxy C 2-4 and compounds in which the phenyl groups in these compounds are replaced with biphenyl groups to form biphenyl groups (9,9-bis[3-phenyl-4-(2-(meth)acryloyloxyethoxy)phenyl])fluorene, etc. 9,9-bis[phenyl-(meth)acryloyloxy C 2-4alkoxyphenyl] fluorenes, etc.; compounds in which the naphthyl group is (9,9-bis[5 or 6-(2-(meth)acryloyloxyethoxy)-2-naphthyl]) fluorene, 9,9-bis[5 or 6-(2-(meth)acryloyloxyethoxy)-1 or 2-naphthyl)] fluorene, etc. 9,9-bis[((meth)acryloyloxy C 2-4 Alkoxy)naphthyl]fluorenes, etc. As the above (A), only one kind may be used, or two or more kinds may be used.

[0040] The content (content ratio) of (A) in the curable composition of the present disclosure is not particularly limited, but is preferably 10 to 70% by mass, more preferably 20 to 60% by mass, and even more preferably 20 to 50% by mass, relative to the total amount (100% by mass) of the curable composition.

[0041] In addition, the mixing ratio of the above-mentioned (A) and the above-mentioned (B) (former / latter (mass ratio)) is, for example, about 0.2 / 1 to 4 / 1, preferably 0.5 / 1 to 3 / 1, and more preferably 0.8 / 1 to 2.5 / 1. By containing the above-mentioned (A) and the above-mentioned (B) in the above-mentioned range, it is possible to impart more excellent optical properties (excellent transparency, high refractive index) and workability to the cured product. When the ratio of (A) / (B) is less than 4 / 1 in the above-mentioned range, the curable composition has sufficient fluidity and tends to have excellent workability. When the ratio of (A) / (B) is 0.2 / 1 or more, there is a tendency to obtain an effect of improving optical properties.

[0042] <Sulfur atom-containing (meth)acrylate (B)>

[0043] The sulfur-containing (meth)acrylate (B) in the curable composition of the present disclosure is a radical-curable compound (a radical-polymerizable curable compound) containing a sulfur atom and a radical-polymerizable (meth)acryloyl group in the molecule. From the viewpoint of exerting a high refractive index of the cured product and a low viscosity of the curable composition, the number of functional groups in (B) is preferably 2 or more, and in order to have a moderate hardness when cured, it is preferably 4 or less.

[0044] By making the curable composition of the present disclosure contain compound (B), the viscosity of the curable composition can be kept low enough to be easy to handle, and further, the cured product obtained by curing the curable composition can be given excellent optical properties (transparency, high refractive index). As the above (B), a compound represented by the following formula (2) can be cited.

[0045] [Chemical formula 2]

[0046]

[0047] In the above formula (2), R 5 represents a methylene group in which one or two hydrogen atoms are optionally substituted by an alkyl group having 1 to 5 carbon atoms, a sulfur atom, or an oxygen atom. 6 , R 7 The same or different, represents a hydrogen atom or a methyl group. 3 , X 4 are the same or different and represent a sulfur atom or an oxygen atom. 5 , X 3 , X 4 Preferably, at least one of the above contains a sulfur atom.

[0048] As R 5 The methylene group in which one or two hydrogen atoms are optionally replaced by an alkyl group having 1 to 5 carbon atoms includes, for example, a methylene group (unsubstituted methylene group), and a methylene group in which one or two hydrogen atoms are replaced by a group selected from a linear or branched alkyl group such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a pentyl group, etc. When two hydrogen atoms in the methylene group are replaced by an alkyl group having 1 to 5 carbon atoms, the two alkyl groups having 1 to 5 carbon atoms may be the same or different. Specific examples of the methylene group in which one or two hydrogen atoms are replaced by an alkyl group having 1 to 5 carbon atoms include, for example, dimethylmethylene and methylmethylene.

[0049] Typical examples of the curable compound (B) include compounds represented by the following formulae (b1) to (b12).

[0050] [Chemical formula 3]

[0051]

[0052] In the curable composition of the present disclosure, from the viewpoint of excellent workability and being able to form a cured product having more excellent optical properties (transparency, high refractive index), among the above (B), the above formulas (b1) and (b2) having a bis(4-(meth)acryloylthiophenyl)sulfide skeleton are preferred, and (b2) having a bis(4-methacryloylthiophenyl)sulfide skeleton is particularly preferred.

[0053] In the curable composition of the present disclosure, the above-mentioned (B) may be used alone or in combination of two kinds.

[0054] The content (content ratio) of (B) is preferably 5 to 50% by mass, more preferably 10 to 40% by mass, and further preferably 15 to 30% by mass, relative to the total amount (100% by mass) of the curable composition disclosed herein. When the content of (B) is within the above range, a viscosity that is easy to handle is easily obtained when the curable composition is prepared, and a high refractive index is easily obtained when the cured product is prepared.

[0055] <Nano-zirconia particles (C)>

[0056] The curable grease composition of the embodiment of the present disclosure contains nano zirconium oxide particles as the component (C). In the present disclosure, nano zirconium oxide particles refer to zirconium oxide particles whose mode diameter of primary particles in the particle size distribution determined by particle size distribution measurement is 1 μm or less. As (C), it can be obtained by subjecting an aqueous solution containing zirconium hydroxide obtained by neutralization reaction of an aqueous zirconium salt solution and an alkaline aqueous solution to a hydrothermal reaction at a temperature of 200 to 400°C and a pressure of 20 to 40 MPa. With regard to the particle size distribution of the primary particles and secondary particles of (C), the desired particle size distribution can be obtained, for example, by adjusting the temperature and pressure used in the above-mentioned hydrothermal reaction.

[0057] The mode diameter of the primary particles of the above-mentioned (C) measured by particle size distribution measurement is preferably 1 to 100 nm. In addition, the relative standard deviation of the particle size distribution is preferably 40% or less. That is, when the mode diameter and relative standard deviation of the primary particles are within the above-mentioned range, the dispersibility of the above-mentioned (C) in the resin becomes good, and the transparency of the obtained curable composition can be improved, and the refractive index of the cured product of the above-mentioned curable composition can be improved.

[0058] In addition, the secondary particles of the above (C) preferably have a median particle size of 0.3 to 20 μm and a coefficient of variation of 80% or less as measured by particle size distribution measurement. That is, if the median particle size and coefficient of variation of the secondary particles are within the above range, when the surface treatment of the above (C) is performed, the particles have high uniformity and substantially no agglomerated particles remain. By using the above (C) in a uniform manner, there is a tendency to improve the transparency of the curable composition.

[0059] In addition, the above-mentioned (C) may also be a material coated with an organosilicon compound. There is no particular limitation on the degree of dispersion of (C) when coated with the above-mentioned organosilicon compound as long as the effect of the present disclosure can be exerted. In view of the characteristics of the obtained composition, it is preferred to disperse (monodisperse) (C) in a state close to that of primary particles. There is no particular limitation on the dispersing solvent when (C) is coated with an organosilicon compound. For example, an aqueous solvent such as ethanol or water can be used. The degree of dispersion can be adjusted according to the intensity of stirring during the dispersion treatment, the type of solvent used, etc.

[0060] Examples of the organic silicon compound include vinyl trimethoxysilane, vinyl triethoxysilane, allyl trimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 3-glycidoxypropyl methyl dimethoxysilane, 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 3-glycidoxypropyl triethoxysilane, p-styryl trimethoxysilane, 3-methacryloxypropyl methyl dimethoxysilane, 3-methacryloxypropyl trimethoxysilane, 3-methacryloxypropyl triethoxysilane, 3-acryloxypropyl trimethoxysilane, N-2-(aminoethyl)-3-aminopropyl methyl dimethoxysilane, N-2-(aminoethyl)-3-aminopropyl trimethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-trimethoxysilane, Ethoxysilyl-N-(1,3-dimethylbutylene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride, 3-ureidopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanatepropyltriethoxysilane , methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, phenyltrimethoxysilane, trifluoropropyltrimethoxysilane, cyclohexylmethyldimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, hexyltriethoxysilane, hexamethyldisilazane and other organic silicon compounds. Among them, vinyl trimethoxysilane, vinyl triethoxysilane, p-phenylvinyl trimethoxysilane, 3-methacryloxypropyl methyl dimethoxysilane, 3-methacryloxypropyl trimethoxysilane, 3-methacryloxypropyl triethoxysilane, 3-acryloxypropyl trimethoxysilane are preferred, and 3-methacryloxypropyl methyl dimethoxysilane, 3-methacryloxypropyl trimethoxysilane, 3-methacryloxypropyl triethoxysilane, 3-acryloxypropyl trimethoxysilane are particularly preferred. In addition, as the above-mentioned organosilicon compound, only one kind may be used, or two or more kinds may be used.

[0061] In addition, the surface of the above-mentioned (C) can be modified with hydrocarbons. The above-mentioned modification can use a well-known or commonly used organic modifier. As the above-mentioned organic modifier, it is preferably an organic modifier that can bond the hydrocarbon to the surface of the microparticle, and examples thereof include organic modifiers that allow the formation of ether bonds, ester bonds, bonds via N atoms, bonds via S atoms, metal-C- bonds, metal-C= bonds, and metal-(C=O)- bonds. As the above-mentioned hydrocarbon, the number of carbon atoms is not particularly limited, and an organic modifier with 1 or 2 carbon atoms can also be used, but from the viewpoint of fully exerting the characteristics of the present invention, it is preferably a long-chain hydrocarbon with a chain of 3 or more carbon atoms, for example, a straight chain or branched chain, or a cyclic hydrocarbon with 3 to 20 carbon atoms. In addition, the above-mentioned hydrocarbon may be substituted or may be an unsubstituted hydrocarbon. Examples of the organic modifier include alcohols, aldehydes, ketones, carboxylic acids, esters, amines, thiols, amides, oximes, phosgene, enamines, amino acids, peptides, and sugars, and carboxylic acids are particularly preferred. Specific examples of the organic modifier include pentanol, valeraldehyde, valeric acid, valeramide, pentamethylenemercaptan, hexanol, hexanal, hexanoic acid, hexaamide, hexanethiol, heptanol, heptanal, heptanoic acid, heptamide, heptylmercaptan, octanol, octanal, octanoic acid, octylamide, octylmercaptan, decanol, decanal, decanic acid, decanamide, decanethiol, and the like.

[0062] The above-mentioned (C) may be used in a powder state as a monomer, but is preferably used in a dispersed state in the form of a liquid from the viewpoint of handleability. For example, it is preferably dispersed in a liquid containing a (meth)acrylate.

[0063] The content of the dispersion containing (C) is preferably 10 to 70 mass %, particularly preferably 15 to 60 mass %, and further preferably 20 to 50 mass % relative to the total amount (100 mass %) of the curable composition of the present disclosure.

[0064] <Other monofunctional (meth)acrylate compounds>

[0065] The curable composition of the present disclosure preferably contains other radical polymerizable compounds in addition to the above (A), (B) and (C), and particularly preferably contains a (meth)acrylate compound (other (meth)acrylate compound) as the above other radical polymerizable compound.

[0066] The other (meth)acrylate compound is not particularly limited, and examples thereof include monofunctional (meth)acrylates and polyfunctional (meth)acrylates. In the present disclosure, monofunctional (meth)acrylates are preferred because they can react with (A) and (B) to reduce the viscosity of the curable composition.

[0067] The other monofunctional (meth)acrylate compounds mentioned above are not particularly limited, and examples thereof include: monofunctional (meth)acrylate compounds having an aromatic ring in the molecule (hereinafter, sometimes referred to as "monofunctional (meth)acrylate compounds having an aromatic ring"); monofunctional (meth)acrylate compounds having an alicyclic ring (aliphatic cyclic skeleton) in the molecule, monofunctional (meth)acrylate compounds having a chain aliphatic group in the molecule, etc., and monofunctional (meth)acrylate compounds having an aromatic ring are particularly preferred.

[0068] Examples of the aromatic ring possessed by the monofunctional (meth)acrylate compound having an aromatic ring include a benzene ring, a biphenyl ring, a naphthalene ring, a fluorene ring, an anthracene ring, a stilbene ring, a dibenzothiophene ring, and a carbazole ring. The aromatic ring may be any aromatic ring such as an aromatic carbocyclic ring or an aromatic heterocyclic ring, but preferably contains at least an aromatic carbocyclic ring, and particularly preferably contains a biphenyl ring.

[0069] For the monofunctional (meth)acrylate compound having an aromatic ring, the (meth)acryloyloxy group present in the molecule may be directly bonded to the aromatic ring or may be bonded via other compounds. The other compound is preferably a compound capable of bonding to the aromatic ring and the (meth)acryloyloxy group at both ends thereof, and examples thereof include linking groups having structures such as ethylene glycol, propylene glycol, and diethylene glycol.

[0070] Representative examples of the monofunctional (meth)acrylate compound having an aromatic ring include benzyl acrylate, phenoxydiethylene glycol acrylate, ethoxylated o-phenylphenol acrylate, etc. In addition, such compounds can be used alone or in combination of two or more. These compounds can be mixed with the above (A) and (B) to dissolve the above (A) and (B) and significantly reduce the viscosity of the curable composition, thereby providing fluidity that facilitates operation.

[0071] The content (ratio of content) of the other radical polymerizable compound (particularly the other monofunctional (meth)acrylate compound) relative to the total amount (100% by mass) of the curable composition disclosed herein is not particularly limited, but is preferably 1 to 30% by mass, more preferably 2 to 20% by mass, and further preferably 3 to 10% by mass. By adding within the above range, there is a tendency to further improve the fluidity of the curable composition without reducing the optical properties.

[0072] <Radical polymerization initiator>

[0073] The curable composition of the present disclosure preferably further contains a radical polymerization initiator. As the radical polymerization initiator, any initiator capable of initiating radical polymerization, such as a known or customary thermal radical polymerization initiator and a photoradical polymerization initiator, can be used without particular limitation.

[0074] Examples of the thermal radical polymerization initiator include azo compounds such as azobisisobutyronitrile and organic peroxides. Examples of the organic peroxides include hydroperoxides, dialkyl peroxides, peroxyesters, diacyl peroxides, peroxydicarbonates, peroxyketals, ketone peroxides, and the like (specifically, benzoyl peroxide, tert-butyl peroxy-2-ethylhexanoate, 2,5-dimethyl-2,5-di(2-ethylhexanoyl)peroxyhexane, tert-butyl peroxybenzoate, tert-butyl peroxide, cumene hydroperoxide, dicumyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-dibutylperoxyhexane, 2,4-dichlorobenzoyl peroxide, 1,4-di(2-tert-butylperoxyisopropyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, methyl ethyl ketone peroxide, and 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate).

[0075] Examples of the photoradical polymerization initiator include benzophenone, benzylacetophenone, benzyldimethylketone, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, dimethoxyacetophenone, dimethoxyphenylacetophenone, diethoxyacetophenone, diphenyl disulfide, methyl o-benzoylbenzoate, ethyl 4-dimethylaminobenzoate (trade name "KAYACURE EPA" etc., manufactured by Nippon Kayaku Co., Ltd.), 2,4-diethylthioxanthone (trade name "KAYACURE DETX" etc., manufactured by Nippon Kayaku Co., Ltd.), 2-methyl-1-[4-(methyl)phenyl]-2-morpholinopropanone-1 (trade name "Irgacure 907" etc., manufactured by Ciba-Geigy Co., Ltd.), 1-hydroxycyclohexylphenyl ketone (trade name "Irgacure 184", etc., manufactured by Ciba-Geigy Co., Ltd.), 2-amino-2-benzoyl-1-phenylalkane compounds such as 2-dimethylamino-2-(4-morpholino)benzoyl-1-phenylpropane, tetrakis(tert-butylperoxycarbonyl)benzophenone, benzyl, 2-hydroxy-2-methyl-1-phenylpropane-1-one, aminobenzene derivatives such as 4,4'-bis(diethylamino)benzophenone, 2,2 Imidazole compounds such as '-bis(2-chlorophenyl)-4,5,4',5'-tetraphenyl-1,2'-biimidazole (trade name "B-CIM", etc., manufactured by Hodogaya Chemical Co., Ltd.), halomethylated triazine compounds such as 2,6-bis(trichloromethyl)-4-(4-methoxynaphthalen-1-yl)-1,3,5-triazine, 2-trichloromethyl-5-(2-benzofuran-2-ylvinyl)-1,3,4- Oxadiazole and other halomethyl Oxadiazole compounds, etc. In addition, a photosensitizer may be added as needed.

[0076] It should be noted that, in the curable composition of the present invention, the free radical polymerization initiator can be used alone or in combination of two or more. Among them, as the above-mentioned free radical polymerization initiator, from the viewpoint of being able to use a metal mold with high precision, a thermal free radical polymerization initiator is preferably used. That is, the curable composition of the present invention is preferably a thermosetting composition that is cured by heating to obtain a cured product.

[0077] The content (amount added) of the radical polymerization initiator in the curable composition of the present disclosure is not particularly limited, but is preferably 0.05 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, and even more preferably 0.5 to 4 parts by mass, relative to 100 parts by mass of the total amount of the radical curable compounds contained in the curable composition.

[0078] <Curing Retardant>

[0079] The curable composition of the present invention preferably contains a curing retarder. Examples of the curing retarder include organic compounds such as α-methylstyrene dimer, terpinolene, myricene, limonene, α-pinene, and β-pinene. By adding such a curing retarder, the free radical curing rate of the curable composition of the present invention is appropriately delayed, and the curable composition at any part of the mold is cured at a roughly constant rate, so that a molded product without a wavy wrinkle pattern such as "sink marks" or "lines" can be easily obtained.

[0080] It is generally believed that the corrugated pattern called "sink mark" and "line" is easily generated on the surface of the cured product of the free radical curing composition because there is a tendency for the curing of the curing composition to proceed very quickly in the free radical curing system. In particular, for a curing composition with an excessively fast curing speed, it is easy to produce deviations in the curing speed according to the position in the mold. It can be considered that the above-mentioned problem becomes obvious when the curing shrinkage is uneven. There are many cases where such problems occur significantly in the casting molding using the free radical curing system. When such a striped pattern is generated on the surface of an optical component such as a lens, the optical properties of the product cannot be uniformly exerted, which will cause a significant reduction in the commodity value. When a curing retarder is combined with the curing composition (free radical curing compound) disclosed in the present invention, the curing speed is appropriately delayed, and the curing reaction is performed in the same manner at any position of the cured product. Regardless of the position, the curing compound is cured at a certain speed, and therefore, a cured product having a wrinkle pattern such as "sink mark" and "line" and the like that is suppressed on the surface of the molded product formed by the resin cured product can be formed.

[0081] The curing retardant is preferably a curing retardant that has sufficient compatibility with the curable composition and can maintain high transparency without causing haziness such as white turbidity in the curable composition or the cured product. Among them, α-methylstyrene dimer is preferred.

[0082] The content (amount added) of the curing retarder in the curable composition of the present disclosure is not particularly limited, but is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 4 parts by mass, and even more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the total amount of the radical curable compound contained in the curable composition.

[0083] The curable composition of the present disclosure preferably contains the above-mentioned other monofunctional (meth)acrylate in addition to the above-mentioned (A) to (C). By containing the above-mentioned other monofunctional (meth)acrylate, it is possible to maintain a high refractive index and to achieve excellent handling properties and storage stability.

[0084] In addition, the curable composition of the present disclosure preferably contains a radical polymerization initiator and a curing retardant in addition to the above (A) to (C). By containing these two components, the curing reaction can be adjusted and suitable for molding of lenses and the like.

[0085] <Other compounds>

[0086] In the range that does not impair the effect of the present disclosure, the curable composition of the present disclosure may contain curable compounds other than the above-mentioned components (hereinafter sometimes referred to as "other compounds") as needed. As other compounds, as other components, for example: cationic curable compounds, cationic polymerization initiators, curing agents, curing accelerators, various additives, etc. can be listed. In addition, the sum of the contents of (A) to (C) in the curable composition of the present disclosure is preferably, for example, 70% by mass or more of the total amount of the curable composition (100% by mass), preferably 80% by mass or more, and more preferably 90% by mass or more. Therefore, relative to the total amount of the curable composition (100% by mass), the content of other compounds is, for example, 30% by mass or less, preferably 20% by mass or less, and more preferably 10% by mass or less. When the content of other curable compounds is higher than the above range, there is a tendency that it is difficult to obtain the effect of the present disclosure.

[0087] As the above-mentioned cationic curable compound, for example, epoxy compounds having an aromatic ring, oxetane compounds, vinyl ether compounds, etc. can be listed, specifically, epibis (epi-bis) type glycidyl ether type epoxy compounds, epoxy compounds having a bisarylfluorene skeleton, etc. can be listed. By containing a cationic curable compound, it is sometimes possible to reduce the viscosity of the curable composition and inhibit the curing shrinkage of the cured product. The content (compounding amount) of the cationic curable compound in the curable composition of the present invention is not particularly limited, and is preferably 0 to 30% by mass, more preferably 5 to 30% by mass, and further preferably 5 to 15% by mass, relative to the total amount (100% by mass) of the curable composition.

[0088] As the above-mentioned additives, known or commonly used additives can be used without particular limitation, and examples thereof include: organosiloxane compounds, metal oxide particles, rubber particles, silicone or fluorine-based defoamers, silane coupling agents, fillers, plasticizers, leveling agents, antistatic agents, mold release agents, flame retardants, colorants, antioxidants, ultraviolet absorbers, ion adsorbents, pigments, etc. The content (compounding amount) of these various additives is not particularly limited, and is preferably 5% by mass or less relative to the total amount (100% by mass) of the curable composition.

[0089] In addition, the curable composition of the present disclosure may also contain an organic solvent. If the organic solvent is too much, bubbles may be generated in the cured product. Therefore, the organic solvent is preferably 10% by mass or less, and more preferably 1% by mass or less relative to the total amount (100% by mass) of the curable composition.

[0090] The curable composition of the present disclosure can be prepared by a known or customary method, without particular limitation, and can be prepared by mixing a given amount of a curable compound, a free radical polymerization initiator, a curing retarder, other components, etc., as needed, and then removing bubbles as needed, for example, under vacuum, and stirring / mixing. The temperature during stirring / mixing is not particularly limited, and is preferably about 10 to 60° C. For stirring / mixing, known or customary devices such as a rotation-revolution type mixer, a single screw or multi-screw extruder, a planetary mixer, a kneader, a dissolver, etc. can be used.

[0091] [cured material]

[0092] The cured product of the present disclosure can be obtained by curing the above-mentioned curable composition. Curing can be performed, for example, by subjecting the curable composition to light irradiation and / or heat treatment.

[0093] The light irradiation is preferably performed using, for example, a mercury lamp, a xenon lamp, a carbon arc lamp, a metal halide lamp, sunlight, an electron beam source, a laser light source, an LED light source, etc., with a cumulative irradiation dose of, for example, 500 to 5000 mJ / cm 2 As the light source, UV-LED (wavelength: 350 to 450 nm) is preferred.

[0094] The heat treatment is preferably performed at a temperature of, for example, about 100 to 200° C. (preferably 120 to 160° C.) for a short time (for example, about 1 to 10 minutes, preferably 1 to 3 minutes).

[0095] After the light irradiation and / or heat treatment is completed, it is preferable to further perform an annealing treatment to eliminate the internal strain. For example, it is preferable to perform heating at a temperature of 100 to 200° C. for about 30 minutes to 1 hour.

[0096] The cured product of the present disclosure has excellent transparency, and the transmittance of light having a wavelength of 450 nm is, for example, 70% or more, preferably 75% or more, and more preferably 80% or more.

[0097] The refractive index of the above-mentioned cured product under the conditions of 25°C and a wavelength of 589nm is preferably 1.65 or more, and more preferably 1.651 or more. By making the refractive index above 1.65, it is suitable to impart functions such as anti-reflection and optical waveguide when used as a wafer lens. In addition, it is possible to impart functions such as low curvature, thinness and lightness to the lens surface. Specifically, by setting the refractive index of the above-mentioned cured product to above 1.65, the refraction at the lens interface increases, so that the depth of the shape can be made gentle. As a result, the curvature of the lens surface can be reduced, and the thickness can be designed to be thinner, so that the amount of material used can be reduced to achieve lightness. In addition, since the curvature can be reduced, it is not easily affected by the shrinkage rate, and the molding processability is also improved.

[0098] [Optical components]

[0099] The cured product of the present disclosure can be preferably used as an optical component. The optical component of the present disclosure includes optical components [flash lens, light diffusion lens, camera lens or sensor lens (especially Fresnel lens), prism, etc.] used for portable electronic devices (smartphones, tablet terminals, etc.), vehicle-mounted electronic devices, various sensors (infrared sensors, etc.), etc.

[0100] The optical component disclosed in the present invention has sufficient heat resistance for substrate mounting through high-temperature heat treatment (for example, high-temperature treatment above 260°C such as reflow soldering). Therefore, an optical device having the optical component disclosed in the present invention does not need to install the optical component in another process, and the optical component and other components can be mounted on the substrate at one time through high-temperature heat treatment (for example, reflow soldering), and can be manufactured efficiently and at low cost. That is, the optical component disclosed in the present invention can be preferably used as an optical component for reflow soldering mounting. In addition, due to its excellent heat resistance, it can also be used as an optical component in vehicle-mounted electronic equipment.

[0101] Furthermore, since the optical member of the present disclosure has excellent optical characteristics, it is possible to maintain excellent optical characteristics even if it is mounted on a substrate at once with other members by high-temperature heat treatment (for example, reflow soldering).

[0102] [Manufacturing method of wafer-level lens]

[0103] The curable composition of the present disclosure is cured and molded to obtain a wafer-level lens. Specifically, the wafer-level lens of the present disclosure can be obtained by subjecting the curable composition of the present disclosure to a casting molding method or an injection molding method.

[0104] It should be noted that the material of the mold used for molding the wafer-level lens (wafer-level lens molding mold) is not particularly limited, and may be any material such as metal, glass, plastic, etc.

[0105] <Casting method>

[0106] As the above-mentioned casting method, for example, there can be mentioned a method including the following steps 1a to 3a.

[0107] Step 1a: a step of preparing a wafer-level lens molding mold having one or more lens molds;

[0108] Step 2a: After step 1a, a step of bringing the curable composition of the present disclosure into contact with the above-mentioned wafer-level lens molding mold;

[0109] Step 3a: After step 2a, a step of curing the curable composition of the present disclosure by heating and / or irradiation with light (either or both of heating and irradiation with light).

[0110] The curing of the curable composition disclosed in the present invention can be carried out by heat treatment and / or light irradiation (step 3a). In the case of heat treatment, the temperature can be appropriately adjusted according to the components provided for the reaction, the type of catalyst, etc., and is not particularly limited, preferably 100 to 200°C, more preferably about 120 to 160°C. In the case of light irradiation, as the light source, for example, a mercury lamp, a xenon lamp, a carbon arc lamp, a metal halide lamp, sunlight, an electron beam source, a laser light source, etc. can be used. In addition, after light irradiation, for example, heat treatment can be carried out at a temperature of about 50 to 180°C to further carry out the curing reaction.

[0111] The above-mentioned casting method may further include the following step 4a after step 3a.

[0112] Step 4a: a step of annealing the cured curable composition of the present disclosure.

[0113] The annealing treatment is not particularly limited, and can be performed, for example, by heating at 100 to 200° C. for about 30 minutes to 1 hour. It should be noted that the annealing treatment may be performed after or without removing the wafer level lens molding mold.

[0114] The above-mentioned casting molding method, especially when implemented by the simultaneous molding method described later, can usually obtain a sheet-like solidified product (wafer-level lens sheet) formed in a state where one or more wafer-level lenses are connected through the above-mentioned step 3a or step 4a. In the case where the above-mentioned wafer-level lens sheet has multiple wafer-level lenses, these wafer-level lenses can be arranged in an orderly manner (aligned) or randomly arranged. By cutting the above-mentioned wafer-level lens sheet and removing the excess part, the wafer-level lens disclosed in the present invention can be obtained.

[0115] That is, when the above-mentioned casting molding method is particularly performed by the simultaneous molding method described later, the above-mentioned casting molding method may further include the following step 5a after the step 3a or the step 4a.

[0116] Step 5a: a step of cutting the cured curable composition of the present disclosure (generally, a wafer-level lens sheet).

[0117] The curable composition of the present disclosure after curing can be cut by a known or customary processing method or the like.

[0118] More specifically, the casting molding method includes a simultaneous molding method including the following steps 1-1 to 1-3, a single-piece molding method including the following steps 2-1 and 2-2, and the like.

[0119] (Simultaneous molding method)

[0120] Step 1-1: pouring the curable composition of the present disclosure into a wafer-level lens molding mold having a shape in which a plurality of lens molds are aligned in a certain direction, and curing the composition by heating and / or irradiating light;

[0121] Step 1-2: After step 1-1, the wafer-level lens molding mold is removed and annealed to obtain a cured product (wafer-level lens sheet) having a shape formed by combining a plurality of wafer-level lenses;

[0122] Step 1-3: After step 1-2, a step of cutting the obtained cured product to obtain a wafer-level lens.

[0123] (Single-piece molding method)

[0124] Step 2-1: a step of pouring the curable composition of the present disclosure into a wafer-level lens molding mold having one lens mold, and curing it by heating and / or irradiating light;

[0125] Step 2-2: After step 2-1, the wafer-level lens forming mold is removed and annealing treatment is performed to obtain a wafer-level lens.

[0126] <Injection molding method>

[0127] As the injection molding method, for example, there can be mentioned a method including the following steps 1b to 3b.

[0128] Step 1b: a step of preparing a wafer-level lens molding mold having one or more lens molds;

[0129] Step 2b: After step 1b, a step of injecting the curable composition of the present disclosure into the above-mentioned wafer-level lens molding mold;

[0130] Step 3b: a step of curing the curable composition of the present disclosure by heating and / or light irradiation after step 2b.

[0131] The curing of the curable composition of the present disclosure in the above-mentioned injection molding method can be performed by heat treatment and / or light irradiation, and more specifically, can be performed in the same manner as the curing in the above-mentioned cast molding method.

[0132] The above-mentioned injection molding method may further include the following step 4b after step 3b.

[0133] Step 4b: a step of annealing the cured curable composition of the present disclosure.

[0134] The annealing treatment is not particularly limited, and can be performed, for example, by heating at 100 to 200° C. for about 30 minutes to 1 hour. It should be noted that the annealing treatment may be performed after or without removing the wafer level lens molding mold.

[0135] The injection molding method may further include a step of removing burrs after step 3b or step 4b.

[0136] In the simultaneous molding method in the above-mentioned casting molding method, from the viewpoint of excellent filling property into the wafer-level lens molding mold, the curable composition of the present invention is preferably low in viscosity and excellent in fluidity. The viscosity of the curable composition of the present invention used in the above-mentioned simultaneous molding method at 25°C is not particularly limited, but is preferably 10000 mPa·s or less, and more preferably 5000 mPa·s or less. By adjusting the viscosity of the curable composition of the present invention to the above-mentioned range, the fluidity is improved, bubbles are less likely to remain, and the filling into the wafer-level lens molding mold can be performed while suppressing the increase in injection pressure. That is, the coating and filling properties can be improved, and the workability can be improved in the entire molding operation of the curable composition of the present invention.

[0137] The wafer-level lens disclosed in the present invention can be used as a constituent member of a stack of multiple wafer-level lenses (sometimes referred to as a "stacked wafer-level lens"). That is, the stacked wafer-level lens disclosed in the present invention is a stacked wafer-level lens having at least the wafer-level lens disclosed in the present invention as a wafer-level lens constituting the stacked wafer-level lens. It should be noted that the wafer-level lenses constituting the stacked wafer-level lens disclosed in the present invention may all be the wafer-level lenses disclosed in the present invention, or may be the wafer-level lenses disclosed in the present invention and other wafer-level lenses. The number of wafer-level lenses constituting the stacked wafer-level lens disclosed in the present invention is not particularly limited, and is, for example, 2 to 5 pieces (particularly 2 to 3 pieces).

[0138] The stacked wafer-level lens disclosed in the present invention can be manufactured by a known or customary method without any particular limitation. For example, it can be manufactured by stacking a plurality of wafer-level lenses including the wafer-level lens disclosed in the present invention, or it can be manufactured by cutting a wafer-level lens sheet stack (a stack of wafer-level lens sheets), wherein the wafer-level lens sheet stack is obtained by stacking a plurality of wafer-level lens sheets including wafer-level lens sheets obtained by the above-mentioned simultaneous molding method. It should be noted that in the stacked wafer-level lens disclosed in the present invention (or the above-mentioned wafer-level lens sheet stack), each wafer-level lens (or each wafer-level lens sheet) can be joined by a known or customary bonding method, or it may not be joined.

[0139] More specifically, the laminated wafer-level lens of the present disclosure can be produced, for example, by a method including at least the following steps 1c to 5c.

[0140] Step 1c: a step of preparing a wafer-level lens molding mold having one or more lens molds;

[0141] Step 2c: After step 1c, a step of bringing the curable composition of the present disclosure into contact with the above-mentioned wafer-level lens molding mold;

[0142] Step 3c: After step 2c, a step of curing the curable composition of the present disclosure by heating and / or irradiating light to obtain a wafer-level lens sheet;

[0143] Step 4c: After step 3c, a step of laminating a plurality of wafer-level lens sheets including the wafer-level lens sheet to obtain a wafer-level lens sheet laminate;

[0144] Step 5c: After step 4c, a step of cutting the wafer-level lens sheet stack.

[0145] The method for manufacturing the stacked wafer-level lens may further include the following step between step 3c and step 4c.

[0146] Step 6c: a step of annealing the wafer-level lens sheet.

[0147] The wafer-level lens or stacked wafer-level lens disclosed in the present invention has excellent heat resistance and optical properties, and can exhibit excellent shape retention and maintain excellent optical properties even when exposed to high temperature environments. Therefore, it is preferably used as a shooting lens for cameras (car cameras, digital cameras, PC cameras, mobile phone cameras, surveillance cameras, etc.) in various optical devices, glasses wafers, beam focusing lenses, light diffusion lenses, etc. The above-mentioned optical device equipped with the wafer-level lens or stacked wafer-level lens disclosed in the present invention has high quality.

[0148] Furthermore, when the wafer-level lens or stacked wafer-level lens of the present invention is mounted on a circuit substrate, it can be soldered and mounted by reflow. Therefore, a camera module equipped with the wafer-level lens or stacked wafer-level lens of the present invention can be directly and very efficiently mounted on a PCB (Printed Circuit Board) substrate of a mobile phone or the like by the same reflow soldering process as the surface mounting of other electronic components, which can realize the manufacture of extremely efficient optical devices.

[0149] Each method disclosed in this specification can be combined with any other features disclosed in this specification. In addition, each configuration and their combination in each embodiment is an example, and addition, omission and other changes of the configuration can be appropriately made within the scope of the main purpose of the present disclosure. The present disclosure is not limited by the embodiments, but only by the claims.

[0150] Example

[0151] Hereinafter, one embodiment of the present disclosure will be described in more detail based on examples.

[0152] [Curable composition]

[0153] Example 1, Comparative Example 1

[0154] The components described in Table 1 were blended according to the blending composition described in Table 1 (values ​​are parts by mass), and stirred and mixed using an autorotation-revolution type mixer at room temperature to obtain a uniform and transparent curable composition (radical curable composition).

[0155] (Details of each ingredient)

[0156] Fluorene skeleton-containing (meth)acrylate (A): a compound containing a 9,9-bis[4-[2-(acryloyloxy)ethoxy]phenyl]fluorene skeleton, trade name "HIC-G722D", manufactured by Kyoeisha Chemical Co., Ltd.

[0157] Sulfur-containing (meth)acrylate (B): a product containing bis(4-methacryloylthiophenyl)sulfide, manufactured by Tokyo Chemical Industry Co., Ltd.

[0158] Nano-zirconia-dispersed (meth)acrylate (C): trade name "KZ-D673" (the mode diameter of the nano-zirconia particles contained is 1 to 100 nm), manufactured by Kyoeisha Chemical Co., Ltd.

[0159] Other (meth)acrylates: ethoxylated o-phenylphenol acrylate, trade name "A-LEN-10", manufactured by Shin-Nakamura Chemical Industry Co., Ltd.

[0160] Thermal radical polymerization initiator: containing 80% by mass of 1,1-bis(tert-butylperoxy)cyclohexane, trade name "PERHEXA C-80", manufactured by NOF Corporation

[0161] Curing retarder: 2,4-diphenyl-4-methyl-1-pentene, trade name "α-MSD", manufactured by Tokyo Chemical Industry Co., Ltd.

[0162] Next, the curable compositions obtained in Examples and Comparative Examples were cured by the following heat treatment method to obtain cured products.

[0163] <Heat treatment method>

[0164] An imprint molding machine (trade name "NANOIMPRINTER NM-0501", manufactured by Meichang Machinery Co., Ltd.) was used to perform curing / molding with a thickness of 0.5 mm according to the following molding information, and the mold was released after cooling to 80°C. It was further heated in an oven preheated to 160°C for 30 minutes to perform annealing treatment to obtain a cured product.

[0165] The following evaluations were performed on the obtained curable compositions and cured products.

[0166] [evaluate]

[0167] (1) Viscosity

[0168] The viscosity of the curable composition was measured using a rheometer (trade name "PHYSICA UDS200", manufactured by Paar Physica), and the viscosity was defined as the viscosity (mPa·s) at 25° C. and a rotation speed D=20 / s.

[0169] (2) Refractive index

[0170] The refractive index of the cured product at 589 nm at 25° C. was measured using a refractometer (trade name “Prism Coupler 2010 / M”, manufactured by METRICON).

[0171] (3) Transmittance

[0172] The external transmittance of the cured product at 450 nm was measured using an ultraviolet-visible spectrophotometer (trade name "U-3900H", manufactured by Hitachi High-Technologies Corporation).

[0173] (4) Liquid stability

[0174] After the above curable composition was prepared, the state of the liquid after being stored under refrigeration (0° C.) for one week was evaluated as follows.

[0175] ○: Transparent, no fuzzy precipitate

[0176] ×: There is a fuzzy precipitate

[0177] [Table 1]

[0178]

[0179] Modifications of the disclosed invention are described below.

[0180] [Appendix 1]

[0181] A curable composition contains a (meth)acrylate containing a fluorene skeleton, a (meth)acrylate containing a sulfur atom, and nano zirconium oxide particles.

[0182] [Appendix 2]

[0183] The curable composition according to Appendix 1, further comprising other monofunctional (meth)acrylate.

[0184] [Appendix 3]

[0185] The curable composition according to Appendix 1 or 2, wherein when cured, the curable composition has a refractive index of 1.65 or more at a wavelength of 589 nm.

[0186] [Appendix 4]

[0187] The curable composition according to any one of Appendices 1 to 3, wherein the viscosity at 25° C. is 10000 mPa·s or less.

[0188] [Appendix 5]

[0189] The curable composition according to any one of Appendixes 1 to 4, wherein the sulfur atom-containing (meth)acrylate has a bis(4-(meth)acryloylthiophenyl)sulfide skeleton.

[0190] [Appendix 6]

[0191] The curable composition according to any one of Appendixes 1 to 5, wherein the mode diameter of the nano-zirconia particles measured by particle size distribution measurement is 1 to 100 nm.

[0192] [Appendix 7]

[0193] The curable composition according to any one of Appendixes 1 to 6, which is used for a wafer lens.

Claims

1. A curable composition comprising: (Meth)acrylate containing a fluorene skeleton, Sulfur-containing (meth)acrylates, and Nano-zirconia particles. 2 . The curable composition according to claim 1 , further comprising another monofunctional (meth)acrylate. 3 . The curable composition according to claim 1 , which has a refractive index of 1.65 or more at a wavelength of 589 nm when cured. The curable composition according to claim 1 or 2, which has a viscosity at 25°C of 10,000 mPa·s or less.

5. The curable composition according to claim 1 or 2, wherein The sulfur atom-containing (meth)acrylate has a bis(4-(meth)acryloylthiophenyl)sulfide skeleton.

6. The curable composition according to claim 1 or 2, wherein The mode diameter of the nano zirconium oxide particles measured by particle size distribution measurement is 1 to 100 nm. 7 . The curable composition according to claim 1 , which is a curable composition for a wafer lens.

Citation Information

Patent Citations

  • Photocurable high refractive index resin composition

    JP2019019245A

  • Heat collector

    JP2022094012A

  • Curable composition for wafer level lenses, method for producing wafer level lens, wafer level lens, and optical device

    WO2014119424A1

  • Curable composition and cured product

    WO2018062196A1